2010
DOI: 10.1093/eurjhf/hfq057
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial gene expression alterations in peripheral blood mononuclear cells of patients with idiopathic dilated cardiomyopathy

Abstract: AimsTo assess cardiac gene expression in peripheral blood cells of patients with idiopathic dilated cardiomyopathy (IDCM) and its relationship to echocardiographic left ventricular (LV) function. Methods and resultsA complete echocardiographic study and blood sampling were performed in 65 consecutive stable IDCM patients with LV ejection fraction (LVEF) 31.76 + 10.07% and chronic mild to moderate heart failure (NYHA functional class II to III) for ≥9 months. Blood samples from 19 healthy individuals were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Levels of MYOCD mRNA were first shown to be elevated in humans with DCM as compared to normal hearts[81]. Moreover, there have been a series of clinical studies showing increases in MYOCD mRNA in circulating cells or cardiac tissue from patients with idiopathic cardiomyopathy[121],[122], hypertrophic cardiomyopathy[123], and essential hypertension[124]. Interestingly, variants in the 5′ promoter region of human MYOCD were associated with reduced levels of circulating MYOCD , which correlated with attenuated left ventricular mass in hypertrophic cardiomyopathy patients[125].…”
Section: Pathological Processes Linked To Myocardinmentioning
confidence: 99%
“…Levels of MYOCD mRNA were first shown to be elevated in humans with DCM as compared to normal hearts[81]. Moreover, there have been a series of clinical studies showing increases in MYOCD mRNA in circulating cells or cardiac tissue from patients with idiopathic cardiomyopathy[121],[122], hypertrophic cardiomyopathy[123], and essential hypertension[124]. Interestingly, variants in the 5′ promoter region of human MYOCD were associated with reduced levels of circulating MYOCD , which correlated with attenuated left ventricular mass in hypertrophic cardiomyopathy patients[125].…”
Section: Pathological Processes Linked To Myocardinmentioning
confidence: 99%
“…In adult heart, SERCA2 expression levels are highly associated with cardiac functions, therefore, SERCA2 could be used as a marker for detection of cardiomyopathy (Castilho et al, 2007;Andersson et al, 2009;Dai and Rabinovitch, 2009;Kontaraki et al, 2010;Stokke et al, 2010;Summerfield et al, 2010). We have shown that atp2a2a transcripts were detected strongly in the developing heart of 18-96 hpf zebrafish embryos (Fig.…”
Section: Atp2a2a Might Play Important Roles During Heart Development mentioning
confidence: 77%
“…Sarcoplasmic Endoplasmic Reticulum Ca 2+ ATPase (SERCA) is considered a major player in these processes [10]. Indeed, patients with AF have lower SERCA levels compared to patients with sinus rhythm [13]. Of note, SERCA levels can be assayed in peripheral blood lymphocytes, as their levels correlate with SERCA levels obtained in specimens of cardiac tissue [13].…”
Section: Introductionmentioning
confidence: 99%